(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
The role and impact of Dance Movement Therapy (DMT) in enhancing emotional wellbeing and strengthening mental health leads back to the roots of this profession and the pioneer Marian Chace, who started her career at St. Elisabeth’s Hospital in 1942 where psychological casualties of World War II were beginning to fill the wards. It was there that ‘Dance for Communication’ was first offered and was the start of what became a new mental health profession called Dance Movement Therapy. The joint Master’s degree programme in Dance Movement Therapy at the Vilnius University Faculty of Medicine & the Lithuanian Academy of Music and Theatre started in 2019. Since 2021, master’s theses in Dance Movement Therapy have explored its application across several thematic areas: mental health and emotional wellbeing; embodiment, identity, and self-exploration; women’s health and life transitions; physical conditions, disability, and pain; eating disorders and body image; occupational and everyday contexts, and creative modalities and ritual. This presentation focuses on 13 master’s theses addressing the role of Dance Movement Therapy in supporting adults’ mental health and emotional wellbeing. The analysis is structured into three thematic categories: (1) the effects of Dance Movement Therapy on depression and anxiety, (2) its role in addressing trauma, emotional pain, (3) its impact on loneliness and challenges in social relationships. Findings from quantitative studies demonstrate the effectiveness of Dance Movement Therapy in preventing depression, while qualitative research highlights the diverse ways in which therapeutic movement fosters emotional resilience and provides resources for coping with psychological distress and trauma integration. Together, these studies contribute to a growing body of evidence on the integrative potential of Dance Movement Therapy in adult mental health care.